2016
DOI: 10.1111/cpf.12396
|View full text |Cite
|
Sign up to set email alerts
|

Acute resistance exercise using free weights on aortic wave reflection characteristics

Abstract: Aortic wave reflection characteristics such as the augmentation index (AIx), wasted left ventricular pressure energy (ΔE ) and aortic haemodynamics, such as aortic systolic blood pressure (ASBP), strongly predict cardiovascular events. The effects of acute resistance exercise (ARE) using free-weight exercises on these characteristics are unknown. Therefore, we sought to determine the effects of acute free-weight resistance exercise on aortic wave reflection characteristics and aortic haemodynamics in resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 33 publications
5
28
5
Order By: Relevance
“…Participants' baseline physical activity status, although not reported in all studies, ranged from sedentary to highly physically active. Nine studies (Sharman et al, 2008 ; Fahs et al, 2009 ; Collier et al, 2010 ; Gkaliagkousi et al, 2014 ; Hanssen et al, 2015 ; Kingsley et al, 2016 ; Perdomo et al, 2016 ; Thiebaud et al, 2016 ; Tai et al, 2018 ) reported an a priori sample size calculation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants' baseline physical activity status, although not reported in all studies, ranged from sedentary to highly physically active. Nine studies (Sharman et al, 2008 ; Fahs et al, 2009 ; Collier et al, 2010 ; Gkaliagkousi et al, 2014 ; Hanssen et al, 2015 ; Kingsley et al, 2016 ; Perdomo et al, 2016 ; Thiebaud et al, 2016 ; Tai et al, 2018 ) reported an a priori sample size calculation.…”
Section: Resultsmentioning
confidence: 99%
“…The study designs were variable and included 17 cross-over studies (Kingwell et al, 1997 ; Heffernan et al, 2007c , d ; Barnes et al, 2010 ; Collier et al, 2010 ; Yoon et al, 2010 ; Figueroa and Vicil, 2011 ; Ranadive et al, 2012 ; Ribeiro et al, 2014 ; Hanssen et al, 2015 ; Lefferts et al, 2015 ; Siasos et al, 2016a , b ; Thiebaud et al, 2016 ; Kobayashi et al, 2017 ; Yan et al, 2017 ; Tai et al, 2018 ), 24 pre-post interventions (Heffernan et al, 2006 , 2007a , b ; Lydakis et al, 2008 ; Munir et al, 2008 ; Peres et al, 2010 ; Boutcher et al, 2011 ; Doonan et al, 2011 , 2013 ; Hull et al, 2011 ; Hu et al, 2013 ; Lane et al, 2013 ; Gkaliagkousi et al, 2014 ; Yan et al, 2014 ; Burr et al, 2015 ; Chandrakumar et al, 2015 ; Mak and Lai, 2015 ; Milatz et al, 2015 ; Sugawara et al, 2015 ; Sun et al, 2015 ; Kingsley et al, 2016 ; Melo et al, 2016 ; Moore et al, 2016 ; Perdomo et al, 2016 ) and four randomized, controlled trials utilizing a pharmaceutical/placebo design (Sharman et al, 2008 ; Fahs et al, 2009 ; Campbell et al, 2011 ; Lin et al, 2016 ). Thirty-four studies assessed the effects of aerobic exercise (Table 2 ) and 13 examined the effects of resistance exercise (Table 3 ); two of these studies (Heffernan et al, 2007d ; Collier et al, 2010 ) compared the effects of aerobic vs. resistance exercise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is influenced by the timing and the amplitude of the forward traveling wave and the reflected wave (Wilkinson et al, 2000). Following resistance exercise there appears to be a significant impact on measures of pulse wave reflection (Fahs et al, 2009;Yoon et al, 2010;Kingsley et al, 2017;Tai et al, 2018). This is further supported by the meta-analysis of Pierce et al (2018).…”
Section: Introductionmentioning
confidence: 83%
“…However, while we were excited that our previous study, and data, are used in the meta-analysis by Pierce et al (2018), we do have some concerns. Specifically, our primary concern revolves around the data taken from our article, Tai et al (2018) In our article, Tai et al, the AIx that was published was the peripheral AIx, and we did not correct it for changes in pulse pressure, the review article by Pierce et al cited…”
Section: Concernsmentioning
confidence: 99%